Anti-Tumour Effect of a Chitosan Delivery System for Doxorubicin - Tan, M.; Choong, P.; Dass, Crispin (Trans Tech Publications, Switzerland, 2010)
Used against a variety of tumours, doxorubicin (DOX), causes multiple side-effects in patients, especially in high doses required to control tumour growth. A drug delivery system (DDS) was developed to deliver DOX. Through DOX encapsulation into chitosan DDS, novel DOX microparticles (DMPs) were formed. Multiple optimisation steps produced DMPs which caused tumour cell death. Treatment of mice bearing tumours with DMP decreased tumour growth and spread, with no visible side-effects. There are plans to evaluate this delivery vehicle more closely towards clinical development and testing.